Efektivitas UU No. 41 Tahun 1999 - Tampubolon, Herman Suhandi; Harahap, Sumper Mulia; Dalimunthe, Dermina (Jurnal El-Thawalib, 2021)
According to the theory of effectiveness, the findings found by researchers have not reached the benchmark for the effectiveness of protected forests as confirmed in Law 41 of 1999 Article 47 on Forest Protection. The problem that occurs is the problem that is the main supporter of achieving the effectiveness of forest protection. The effectiveness of law no. 41 of 1999 Article 47 concerning benchmarks for effectiveness in the supervision of protected forests in order to maintain their sustainability. where there are problems faced by the agency responsible for the preservation of protected forests. factors inhibiting the effectiveness of law no. 41 of 1999 concerning Forest Protection is a budget cut since COVID-19 which hinders Forest Protection, then lack of public awareness of forest preservation, and lack of legal firmness from law enforcement officers. According to the theory of effectiveness that has not met the requirements or has not achieved this into a serious problem, lack of personnelForest Police Team (only two people), inadequate supporting facilities/infrastructure.figh siyasa review of the effectiveness of law no. 41 of 1999 concerning Forest Protection emphasizes that humans are able to be responsible for everything that Allah SWT has created. Which is where Allah SWT has forbidden humans to do mischief on earth.